Ocupar, resistir e produzir, também na educação! o MST e a burocracia estatal: negação e consenso - Arlete Ramos dos Santos (2013)
The aim of this work is to analyze the educational administration of the Movimento dos Trabalhadores sem Terra - MST, from the standpoint of the capitalist state bureaucracy, as an element of contradiction, considering that this Movement fights for a paradigm of society that differs from the State. The survey was conducted in nine regional MST in Bahia, namely: North, Northeast, South, Southwest, Down South, Deep South, Reconcavo Baiano, Chapada Diamantina and West. Therefore, we sought to identify how the state bureaucracy is part of the educational process of the MST, through the rational - legal basis, taking into account the Weberian and Marxist perspectives. It was also examined if the management implemented in the schools at the settlements and camps of MST - BA is authoritarian or democratic, seeking to highlight the challenges and conflicts experienced by the manager of education in the Moviment, once he plays the role of director / coordinator along with the bureaucracy state (Municipal Education), in which predominates the proposed education of the capital, and he also act as an activist in the education sector of the MST, which had in its origin the defense of the socia lism and, currently , advocates that the model of society that he defends is still under construction. However, it was shown that, in some respects, the MST negates capitalism, and in others, it adopts it because of the contradictions experienced by being immersed in this system. The chosen path was the use of questionnaires with closed questions from semi - structured interviews, and it was also developed a literature review selecting authors that treat the highlighted categories, using historical and dialect ical materialism as a method of analysis. The reflections based on theoretical assumptions and the collected data indicate that the educational administration of the MST is democratic / participatory, with specificities, geared towards the goal of implemen ting the pedagogical Movement, prevailing in the interviews, a socialist pedagogy. The predominant categories in the fight to ensure the educational proposal of the Movement are autonomy and collective work. However, at the state level, this achievement ha s not yet been effected, since not all of the managers ensure that the MST can implement its proposed education. From the conceptual framework of what is defined as bureaucracy in developed studies, and from the results of the collected data for the purposes of the research, it was confirmed that, according to Santos (2010) hypothesis, the organization form , coordination and systematization of MST do not fit this term. Therefore, from th e space expansion and from the subjects of the survey we confirm that t he MST, in all sectors, found a new way of organization that differs from what is defined as bureaucracy. Therefore, it is confirmed the existence of what Santos (2010) understands as Collective Rationality.